Effect of dietary fish oil on fatty acid deposition and expression of cholesterol homeostasis controlling genes in the liver and plasma lipid profile: comparison of two animal models - Komprda, T; Rozíková, V; Zamazalová, N; Škultéty, O; Vícenová, M; Trčková, M; Faldyna, M (Journal of animal physiology and animal nutrition, 2017)
The objective of the present study was to compare hepatic fatty acid deposition, plasma lipid level and expression of cholesterol homeostasis controlling genes in the liver of rats (Wistar Albino; n = 32) and pigs (Large White × Landrace; n = 32) randomly assigned into two groups of 16 animals each and fed 10 weeks the diet with either 2.5% of fish oil (F; source of eicosapentaenoic and docosahexaenoic acid, EPA+DHA) or 2.5% of palm oil (P; high content of saturated fatty acids; control). F-rats deposited in the liver three times less EPA, but 1.3 times more DHA than F-pigs (p < 0.05). Dietary fish oil relative to palm oil increased PPARα and SREBP-2 gene expression much strongly (p < 0.01) in the pig liver in comparison with the rat liver, but expression of Insig-1 and Hmgcr genes in the liver of the F-pigs relative to the expression of these genes in the liver of the P-pigs was substantially lower (p < 0.01 and p < 0.05 respectively) as compared to rats. When plasma lipid concentration in the F-animals was expressed as a ratio of the plasma concentration in the P-counterparts, dietary fish oil decreased HDL cholesterol less (p < 0.01), but LDL cholesterol and triacylglycerols more (p < 0.05 and p < 0.001 respectively) in rats than in pigs: more favourable effect of fish oil on rat plasma lipids in comparison with pigs can therefore be concluded. Concentration of total cholesterol and both its fractions in the rat plasma was negatively correlated (p < 0.01) with hepatic DHA, but also with unsaturated myristic and palmitic acid respectively. It has been concluded that regarding the similarity of the plasma lipid levels to humans, porcine model can be considered superior; however, using this model, dietary fish oil at the tested amount (2.5%) was not able to improve plasma lipid markers in comparison with saturated palm oil.
Keywords: homeostáza; Gene Expression Regulation; prasata; Swine; Animal Nutritional Physiological Phenomena; fyziologie výživy zvířat; long-chain PUFA n-3; Male; Sus scrofa; Rats, Wistar; Animal Feed; PPAR α; mastné kyseliny; Cholesterol; Homeostasis; mužské pohlaví; potkani Wistar; Fatty Acids; krmivo pro zvířata; dieta; Weight Gain; krysa rodu Rattus; rybí oleje; Rattus norvegicus; cholesterol; lipidy; Animals; Fish Oils; ženské pohlaví; zvířata; regulace genové exprese; Rats; Diet; Lipids; hmotnostní přírůstek; Female